22nd Applied Aerodynamics Conference and Exhibit 2004
DOI: 10.2514/6.2004-5382
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Characteristics and Glide-Back Performance of Langley Glide-Back Booster

Abstract: NASA-Langley Research Center is conducting system level studies on an-house concept of a small launch vehicle to address NASA's needs for rapid deployment of small payloads to Low Earth Orbit. The vehicle concept is a three-stage system with a reusable first stage and expendable upper stages. The reusable first stage booster, which glides back to launch site after staging around Mach 3 is named the Langley Glide-Back Booster (LGBB). This paper discusses the aerodynamic characteristics of the LGBB from subsonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Pamadi et al 11 demonstrated that Cart3D predictions agreed well with wind tunnel data for a winged booster vehicle at most flight conditions, whereas APAS predictions exhibited decreasing accuracy as the angle of attack increased. UDP, the low-speed component of APAS, did not capture the nonlinear aerodynamic behavior observed in the wind tunnel data.…”
Section: Sources Of Datamentioning
confidence: 91%
See 3 more Smart Citations
“…Pamadi et al 11 demonstrated that Cart3D predictions agreed well with wind tunnel data for a winged booster vehicle at most flight conditions, whereas APAS predictions exhibited decreasing accuracy as the angle of attack increased. UDP, the low-speed component of APAS, did not capture the nonlinear aerodynamic behavior observed in the wind tunnel data.…”
Section: Sources Of Datamentioning
confidence: 91%
“…Other applications of multi-fidelity modeling abound, both for aerospace applications 19,20 and otherwise. 21,22 Pamadi et al 11 compared the predictions from two analysis tools, APAS 23 and Cart3D. 14 It should be noted that for low angles of attack (below 10-15 o ), Pamadi found that the vortex-lattice and impact methods of APAS were fairly accurate.…”
Section: Exploring the Design Spacementioning
confidence: 97%
See 2 more Smart Citations
“…[4][5][6] Another study by NASA's Langley Research Center of a glide-back booster also found similar trim problems. 7 Based on these previous studies of similar vehicles, it is clear that trim analysis must be taken into account during the initial phases of vehicle design.…”
Section: Introductionmentioning
confidence: 99%